The land beyond the mists : essays on identity and authority in precolonial Congo and Rwanda - Newbury, David S. (Ohio University Press, 2009)
The horrific tragedies of Central Africa in the 1990s riveted the attention of the world. But these crises did not occur in a historical vacuum. By peering through the mists of the past, the case studies presented in The Land Beyond the Mists illustrate the significant advances to have taken place since decolonization in our understanding of the pre-colonial histories of Rwanda, Burundi, and eastern Congo. Based on both oral and written sources, these essays are important both for their methods-viewing history from the perspective of local actors-and for their conclusions, which seriously challenge colonial myths about the area.